2022
DOI: 10.3389/fbioe.2021.793782
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm-Based Trajectory Optimization for Digital Twin Robots

Abstract: Mobile robots have an important role in material handling in manufacturing and can be used for a variety of automated tasks. The accuracy of the robot’s moving trajectory has become a key issue affecting its work efficiency. This paper presents a method for optimizing the trajectory of the mobile robot based on the digital twin of the robot. The digital twin of the mobile robot is created by Unity, and the trajectory of the mobile robot is trained in the virtual environment and applied to the physical space. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 66 publications
0
55
0
Order By: Relevance
“…Now, more and more intelligent algorithms are used to manipulator control systems (Zhang et al, 2017;Lu, 2018;Jiang et al, 2019b;Huang et al, 2019;Nguyen et al, 2019;Huang et al, 2020;Ozyer, 2020;Sun and Liu, 2020;Liu et al, 2021c;Yu et al, 2021). Due to various factor interferences, such as the environment, the robot cannot be positioned accurately, and the positioning error will gradually increase (Sun et al, 2020b;Ozyer, 2020;Liu X. et al, 2021). Against the problem of uncertainty in the motion control of the manipulator, the manipulator is controlled to obtain the desired position by means of a calculated torque method (He et al, 2019;My and Bein, 2020), which improves the systematic robust to a certain extent.…”
Section: Related Workmentioning
confidence: 99%
“…Now, more and more intelligent algorithms are used to manipulator control systems (Zhang et al, 2017;Lu, 2018;Jiang et al, 2019b;Huang et al, 2019;Nguyen et al, 2019;Huang et al, 2020;Ozyer, 2020;Sun and Liu, 2020;Liu et al, 2021c;Yu et al, 2021). Due to various factor interferences, such as the environment, the robot cannot be positioned accurately, and the positioning error will gradually increase (Sun et al, 2020b;Ozyer, 2020;Liu X. et al, 2021). Against the problem of uncertainty in the motion control of the manipulator, the manipulator is controlled to obtain the desired position by means of a calculated torque method (He et al, 2019;My and Bein, 2020), which improves the systematic robust to a certain extent.…”
Section: Related Workmentioning
confidence: 99%
“…Good performance of ResNet on image recognition and localization tasks showed that characterisation depth is of central importance for many visual recognition tasks. In the following years, excellent feature extraction networks such as ResNeXt, DenseNet, RegNet, SEnet, SKNet, etc ( Xie et al, 2017 ; Liu X. et al, 2021 ; Liu et al, 2021b ; Liu et al, 2021c ; Liu et al, 2021d ; Sun et al, 2020c ; Sun et al, 2020d ). were successively proposed, constantly refreshing the accuracy rate of tasks such as image classification.…”
Section: Data Analysis and Network Designmentioning
confidence: 99%
“…The Active Disturbance Rejection Control (ADRC) algorithm studied in this paper ( Han, 2002 ; Ma et al, 2020 ; Sun et al, 2021 ; Tao et al, 2022b ), which inherits the characteristics of the PID algorithm, does not depend on the accurate model of the control object, while using modern signal processing techniques to improve its control process, unifies external disturbances and system errors as total disturbances, and then estimates and compensates them, which has the advantage of being easy to use in engineering and at the same time has a strong anti-disturbance capability. Depending on the Particle Swarm Optimization (PSO) ( Wang et al, 2013 ; Liu X. et al, 2021 ; Bai et al, 2022 ; Liu et al, 2022b ) which is characterized by fast convergence and high computational efficiency ( Li et al, 2019b ; Jiang et al, 2021b ; Liu et al, 2021c ; Huang et al, 2021 . ), Optimizing the parameters of ADRC using PSO can achieve better control effect.…”
Section: Related Workmentioning
confidence: 99%